Educação a distância: um estudo analítico das políticas governamentais com foco no projeto da Universidade Aberta do Brasil - Pereira, Carlos Eduardo Candido[UNESP]; Bizelli, José Luis [UNESP] (My University, 2012)
The present study at the doctoral level, is in the initial phase of the Program Graduate School of Education UNESP, SP-Araraquara campus. That makes an analysis of government policies in distance education system through the Open University of Brazil (UAB). We present in this moment, the historical background of the creation and expansion of the system of the Open University of Brazil with emphasis on policies of expansion of higher education and also the degree in pedagogy courses offered by the partner universities of the University System in Brazil Open southeast. Among the main objectives of the study is to compare the Brazilian government policies of expansion of higher education with the management and characteristics of undergraduate courses in pedagogy. Partial results indicate a total 51 universities that offer degree courses in pedagogy at UAB system in Brazil, including 12 institutions in the Southeast.

O presente estudo, em nível de doutorado, está em fase inicial no Programa de PósGraduação em Educação Escolar da UNESP, campus de Araraquara-SP. O referido faz uma análise das políticas governamentais em educação a distância por meio do sistema da Universidade Aberta do Brasil (UAB). Apresenta-se, neste momento, o percurso histórico de criação e expansão do sistema da Universidade Aberta do Brasil com ênfase nas políticas de expansão do ensino superior e também os cursos de licenciatura em pedagogia ofertados pelas universidades parceiras do sistema da Universidade Aberta do Brasil na região sudeste. Entre os principais objetivos do estudo está comparar as políticas governamentais brasileiras de expansão do ensino superior com a gestão e as características dos cursos de licenciatura em pedagogia. Os resultados parciais indicam ao todo 51 universidades que ofertam cursos de licenciatura em pedagogia pelo sistema UAB no Brasil, sendo 12 instituições na região sudeste.
Distance education: an analytical study of government policies with focus on design of Open University of Brazil
Keywords: Public Policy; Distance Education; Higher Education; Management; Open University of Brazil; Políticas Públicas; Educação a Distância; Ensino Superior; Gestão; Universidade Aberta do Brasil